Clinical and laboratory features in patients with positive syphilis serology presenting with acute ischemic stroke or transient ischemic attack: a prospective cohort study - Jitpratoom P. (2023)
Background: Neurosyphilis (NS) can lead to acute ischemic stroke (AIS) or transient ischemic attack (TIA). We compared the clinical characteristics and laboratory features among AIS and TIA patients who were syphilis-seronegative (control group) or had latent syphilis (LS) or NS to evaluate their stroke outcome. Methods: This prospective cohort study was conducted on patients who had recently suffered AIS or TIA. After serological syphilis screening, clinical and laboratory data were collected, and brain imaging and spinal tap (serologically syphilis-positive patients only) were performed. Stroke outcome was re-evaluated approximately three months later. Results: The 344 enrolled patients were divided into three groups: control group (83.7%), LS (13.1%), and NS (3.2%). A multivariate analysis revealed: 1) age of ≥ 70 years, generalized brain atrophy via imaging, and alopecia (adjusted odds ratio [AOR] = 2.635, 2.415, and 13.264, respectively) were significantly associated with LS vs controls; 2) age of ≥ 70 years (AOR = 14.633) was significantly associated with NS vs controls; and 3) the proportion of patients with dysarthria was significantly lower (AOR = 0.154) in the NS group than in the LS group. Regarding the NS patient cerebrospinal fluid (CSF) profile, only 2/11 cases had positive CSF-Venereal Disease Research Laboratory (VDRL) test results; the other nine cases were diagnosed from elevated white blood cell counts or protein levels combined with positive CSF fluorescent treponemal antibody absorption (FTA-ABS) test results. Regarding disability, the initial modified Rankin scale (mRS) score was lower in the control group than in the NS group (p = 0.022). At 3 months post-stroke, the mRS score had significantly decreased in the control (p < 0.001) and LS (p = 0.001) groups. Regarding activities of daily living, the 3-month Barthel Index (BI) score was significantly higher in control patients than in LS (p = 0.030) or NS (p = 0.002) patients. Additionally, the 3-month BI score was significantly increased in the control (p < 0.001) and LS (p = 0.001) groups. Conclusions: Because syphilis was detected in many AIS and TIA patients, especially those aged ≥ 70 years, routine serological syphilis screening may be warranted in this population. Patients with syphilitic infection had worse stroke outcomes compared with NS patients.